Endoscopic ultrasound-guided fine needle aspiration of solid pseudopapillary tumors of the pancreas: a report of three cases - Park, Hye Yon (The Korean Association of Internal Medicine, 2013)
The solid pseudopapillary tumor (SPT) of the pancreas is a rare but low-grade malignant tumor with a good prognosis after surgical excision. Endoscopic ultrasound (EUS)-guided fine needle aspiration (FNA) is a minimally invasive, safe and reliable way of diagnosing SPT by providing characteristic cytological and immunochemical specimens. Definitive preoperative diagnosis leads to targeted and minimally invasive surgical resection. In this study, we report three cases of SPTs that were diagnosed through EUS-FNA and underwent successful laparoscopic surgery.